Katniss Everdeen’s Act of Rebellion in the Hunger Games Movie - Nur, Frina Diniarta; Adriati, Rini; Wanty, Asri Alvira (STIBA IEC JAKARTA, 2024)
This study is about the analysis of Katniss Everdeen’s Act of Rebellion in the Hunger Games Movie. This study aims to answer three research questions about Katniss Everdeen’s rebellious actions. The first is what are the causes of Katniss's rebellious actions? The second is what are the effects of Katniss's rebellious actions? The third is what are the types of Katniss's rebellion? In this study, the writer uses qualitative research. The writer uses the theory of Marxism by Karl Marx in Tsoulfidis (2010) and the theory of Rebellion by Kautilya (1986). The finding shows 3 (three) causes of Katniss’ Rebellion. They are resource imbalance, provocation, and social inequalities as key factors. Regarding the effects of Katniss‘ rebellion, the finding shows 2 (two) effects. They are negative and positive impacts. Regarding the types of Katniss‘ rebellion, the writer found 5 (five) types of Katniss‘ Rebellion. They are Non-violent rebellion, Violent rebellion, social rebellion, Political rebellion, and Ideological rebellion.